Contextual information in situations of uncertainty: The value of explicit-information provision depends on expertise level, knowledge acquisition and prior-action congruency. (March 2022) - Magnaguagno, Lukas; Zahno, Stephan; Kredel, Ralf; Hossner, Ernst-Joachim
Abstract: In behavioral control, contextual information is used alongside incoming sensory inputs to reduce uncertainties about the unfolding situation. However, our understanding of this weighting process is limited; particularly regarding the applied question of whether individuals should be provided with information or whether they should rather generate it by themselves. We thus compared the provision of more or less valid (i.e., "true") contextual information with a self-generation condition by examining the performance of elite and near-elite youth handball players ( N  = 30 + 27) in a virtual-reality defensive task. We measured response correctness, positioning as a function of the teammates' defensive behaviors and the degree to which the experimentally induced patterns in the teammates' strengths were detected. The results show that providing individuals with uncertain information neither enhances nor harms performance decisively. However, valid information enhances performance in congruent situations while degrading performance in incongruent situations, more pronouncedly in elite than in near-elite players. Consequently, individuals should be provided with explicit contextual information only if (i) their expertise level is not adequate enough to rely on self-generation, (ii) the situation-specific knowledge base cannot be sufficiently self-generated, and (iii) the instructor is sufficiently certain that the explicit information actually meets the upcoming situation. Highlights: Uncertain contextual information neither enhances nor harms players' performance. Providing false information particularly affects elites' behavior negatively. For elite players, self-generated contextual information is a superior source. Providing contextual information requires a sufficient degree of certainty. The merit of explicit information can be estimated by an information-gain function.